PENGARUH PERPUTARAN KAS, PENYALURAN KREDIT, PERTUMBUHAN TABUNGAN DAN DEPOSITO SERTA KECUKUPAN MODAL TERHADAP PROFITABILITAS LPD DI KECAMATAN SUSUT: Studi Empiris pada Lembaga Perkreditan Desa yang ada di Kecamatan Susut - Ni Kadek Lia Likita; I Made Marsa Arsana (Journal Research of Accounting, 2022)
This study aims to examine the effect of cash turnover, credit distribution, growth of savings and time deposits on the profitability of LPD in Susut District. This study uses secondary data. The data was obtained from LPLPD in Susut District and the 2017- 2019 annual financial report. The sample used as many as 39 companies through purposive sampling method. The analytical method used is multiple linear analysis. Based on the results of the study, it was concluded that cash turnover, credit distribution had no effect on profitability, while the growth of savings and time deposits and capital adequacy had a positive effect on profitability. And simultaneously cash turnover, lending, growth in savings and time deposits and capital adequacy simultaneously affect the profitability of LPD.